HEPTAGON FRAUD: DETECTING FRAUDULENT FINANCIAL REPORTING IN INDONESIA’S CONSUMER NON-CYCLICALS SECTOR - Mohamad Zulman Hakim; Apriansyah Saputra; Pugorlillah Rasuan Nanda Pasiraja; Mohamad Vigu Gonzales (PT. ZILLZELL MEDIA PRIMA, 2026)
This study examines the effect of the Fraud Hexagon on fraudulent financial reporting in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the period 2021–2024 using a quantitative approach with panel data regression analysis. The sample consists of 60 companies selected through a purposive sampling method, and fraudulent financial reporting is analyzed in relation to several Fraud Hexagon proxy variables, including financial target, financial stability, external pressure, personal financial need, nature of industry, auditor change, change in directors, effective monitoring, greed, ignorance, and the frequency of CEO photographs. The empirical results show that ignorance, nature of industry, and auditor change have a significant effect on fraudulent financial reporting, while financial target, financial stability, external pressure, personal financial need, change in directors, greed, effective monitoring, and the frequency of CEO photographs do not significantly affect fraudulent financial reporting. These findings indicate that fraud risk in the consumer non-cyclicals sector is driven more by organizational awareness, industry-specific characteristics, and changes in external auditors than by financial pressure or managerial incentives. This study implies that regulators, auditors, and corporate governance mechanisms should prioritize strengthening internal control awareness, improving industry-based risk assessment, and closely monitoring auditor switching to enhance the prevention and detection of fraudulent financial reporting.